2018
DOI: 10.1373/jalm.2017.024828
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput LC-MS/MS Method for Determination of the Alcohol Use Biomarker Phosphatidylethanol in Clinical Samples by Use of a Simple Automated Extraction Procedure—Preanalytical and Analytical Conditions

Abstract: Background: Phosphatidylethanol (PEth) is an alcohol use biomarker with higher clinical sensitivity and specificity than commonly used alcohol markers. Since its introduction as a clinical alcohol-marker in 2006, the number of samples sent to our laboratory for the determination of PEth has shown a strong annual increase. This has prompted the need to develop a cost-effective and reliable analytical procedure with high capacity. Methods: An LC-MS/MS method for the determination of PEth 16:0/18:1 with a short t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…At an EtOH concentration of 50 mmol/l, total PEth, PEth 16:0/18:1, and PEth 16:0/18:2 showed median formation rates of 0.115, 0.034, and 0.042 μ mol/l/h. Thus, PEth 16:0/18:1 and 16:0/18:2 together made up 66% of the total amount of PEth generated, which is compatible with these 2 species being the dominant forms found in blood from individuals consuming alcohol (Helander and Zheng, ; Isaksson et al., ; Nalesso et al., ). A constant EtOH concentration of 25 mmol/l for 24 hours would result in the generation of 0.480 (24 × 0.020 μ mol/l/h; Table ) and 0.576 (24 × 0.024 μ mol/l/h; Table ) μ mol/l/h of PEth 16:0/18:1 and 16:0/18:2 (median values), respectively.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…At an EtOH concentration of 50 mmol/l, total PEth, PEth 16:0/18:1, and PEth 16:0/18:2 showed median formation rates of 0.115, 0.034, and 0.042 μ mol/l/h. Thus, PEth 16:0/18:1 and 16:0/18:2 together made up 66% of the total amount of PEth generated, which is compatible with these 2 species being the dominant forms found in blood from individuals consuming alcohol (Helander and Zheng, ; Isaksson et al., ; Nalesso et al., ). A constant EtOH concentration of 25 mmol/l for 24 hours would result in the generation of 0.480 (24 × 0.020 μ mol/l/h; Table ) and 0.576 (24 × 0.024 μ mol/l/h; Table ) μ mol/l/h of PEth 16:0/18:1 and 16:0/18:2 (median values), respectively.…”
Section: Discussionsupporting
confidence: 58%
“…This is in contrast to previously reported results where PEth formation in heparin blood with added EtOH successively decreased and essentially ceased after 2 days (Schrock et al., ). The in vitro formation of PEth in blood containing EtOH therefore seems to be self‐limiting and without clinical importance as previously shown for blood drawn in EDTA tubes (Isaksson et al., ).…”
Section: Discussionmentioning
confidence: 81%
“…PEth Determination Whole blood concentration of PEth 16:0/ 18:1 was measured by liquid chromatography tandem-mass spectrometry, described in detail previously [19]. There is an agreement between Swedish laboratories on how to report and interpret a PEth value.…”
Section: Methodsmentioning
confidence: 99%
“…There is an agreement between Swedish laboratories on how to report and interpret a PEth value. Thus, no numerical results are reported < 0.05 μmol/L and such values are interpreted as low (moderate) or no consumption, whereas values > 0.30 are interpreted as corresponding to excessive consumption [19,20]. Hence, the limit of quantification was set to 0.05 μmol/ L and used as cut off in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Only at −80°C is the in vitro formation of PEth significantly inhibited (13). However, Isaksson and colleagues (9) concluded that this degree of artefactual PEth formation was clinically insignificant in blood samples collected in EDTA, with only 1 sample showing a PEth value >35 ng/mL (moderate alcohol consumption) when exposed to 0.368 g/dL of ethanol for 3 days, which is >4 times the legal blood alcohol concentration of 0.08 g/dL for driving under the influence or driving while impaired. Nevertheless, laboratories should document the effect of transport time and temperature on this postcollection formation because samples may be received from clients worldwide with transport times of >2 days, unlike the majority of samples obtained in the article.…”
mentioning
confidence: 95%